Collocation and Discursive Construction of Covid-19 in WHO Director General’s Discourse: A Corpus-based Study - Kheovichai, Baramee (LEARN Journal: Language Education and Acquisition Research Network, 2022)
This research investigated the discursive construction of Covid-19 in WHO director general’s discourse through the lens of corpus linguistics and critical discourse analysis. 255 speeches of the WHO director general were collected, forming a 234,149-words corpus. Collocations of ‘Covid-19’ were generated and analyzed in terms of the semantic categories and the representation of Covid-19. The results indicated that Covid-19 was discursively represented as posing severe multifaceted threats to the world. Furthermore, the discursive construction of Covid-19 was found to promote the image of WHO as an active and ethical organization. Thus, discourse was used not only for informational purposes, but it was also manipulated for self-promotion and legitimation.